Osteogenic Differentiation of Renal Interstitial Fibroblasts Promoted by lncRNA MALAT1 May Partially Contribute to Randall’s Plaque Formation - Zhu, Zewu; Huang, Fang; Xia, Weiping; Zeng, Huimin; Gao, Meng; Li, Yongchao; Zeng, Feng; He, Cheng; Chen, Jinbo; Chen, Zhiyong; Li, Yang; Cui, Yu; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: The current belief is that Randall’s plaques (RP) constitute a nidus for the formation of idiopathic calcium oxalate stones, but the upstream events in RP formation remain unclear. The present study aimed to investigate whether RP formation shares similarities with biomineralization and to illustrate the potential role played by the lncRNA MALAT1 in osteogenic differentiation of human renal interstitial fibroblasts (hRIFs). Materials and methods: Biomineralization and MALAT1 expression were assessed in RP, and hRIFs were isolated and induced under osteogenic conditions for further experiments. The transcription initiation and termination sites in MALAT1 were identified by 5′ and 3′ RACE. RNA immunoprecipitation assays and luciferase assays were used to validate the interactions among MALAT1, Runx2 and miRNAs. Results: Upregulated expression of osteogenic markers and MALAT1 was observed in RP and hRIFs induced with osteogenic medium. Biomineralization in RP and calcium phosphate (CaP) deposits in induced hRIFs were further verified by electron microscopy. Furthermore, overexpression of MALAT1 promoted the osteogenic phenotype of hRIFs, while treatment with a miR-320a-5p mimic and knockdown of Runx2 significantly suppressed the osteogenic phenotype. Further analysis showed that MALAT1 functioned as a competing endogenous RNA to sponge miR-320a-5p, leading to upregulation of Runx2 and thus promoting osteogenic differentiation of hRIFs. Conclusions: Ectopic calcification and MALAT1 partially contributed to the formation of RP, in which MALAT1 might promote Runx2 expression to regulate osteogenic differentiation of hRIFs by sponging miRNA-320a-5p. The current study sheds new light on the lncRNA-directed mechanism of RP formation via a process driven by osteogenic-like cells.